Mortality of apricot rootstocks and scions - Mendelné Pászti, Edina; Bujdosó, Géza; Sikwah Narteh, Gideon; Szabó, Zoltán; Mendel, Ákos (Frontiers in Plant Science, 2026)
Aim of our study is to assess the stability and profitability of apricot production by selecting some rootstock and scions among Hungarian climate conditions, that are good adapted to the changing climate. Comparative experiments will be conducted to gain comprehensive knowledge, including their impact on vegetative and generative development, viability, and mortality in new plantations. The experiment utilized a randomized block design, incorporating five rootstocks and 16 apricot scions, resulting in a total of 960 trees planted at a distance of 3 x 5 meters. The survival rate is expressed as a percentage of the initially planted trees for each combination. It can be concluded that rootstocks with vigorous growth, such as ‘Montcar’ and ‘Rootpac R’, were better suited to the climatic and soil conditions of the Hungarian lowlands compared to rootstocks with moderate growth potential, such as ‘Fehér besztercei’ and ‘Wavit’. This is due to their particularly vigorous root growth, which helps to maintain the plantation condition.